Pemasaran Digital Praktis Untuk UMKM: Pendampingan Perempuan Keluarga Nelayan Di Desa Labuhan Burung - Nurasia Nurasia; Irawati Irawati; Sri Andriani; Jannatun Aliyah; Wilia Ismiyarti; Tomy Dwi Cahyono; Ryan Suarantalla; Erwin Mardinata; Hanifa Sri Nuryani (Indonesia Berdampak: Jurnal Pengabdian kepada Masyarakat, 2026)
This community service program aimed to strengthen the digital marketing capacity of fish-processing micro-enterprises in Labuhan Burung Village, Buer District, Sumbawa Regency. The participants were 25 women, mainly spouses of capture-fishery and aquaculture workers, who developed premium and non-premium fish-ball products. The program applied participatory training and practice-based mentoring for approximately four months, covering needs identification, segmentation-targeting-positioning, digital platform selection, AIDA-based content development, product photography, packaging, labeling, and sales communication. Evaluation was descriptive and used participant observation, discussions, documentation, and assessment of practice outputs. The activities indicated that participants were able to distinguish the roles of Facebook, Instagram, TikTok, and WhatsApp; prepare more focused promotional messages; practice product photography; and understand the relationship between packaging, labels, information transparency, and consumer trust. The products have begun to reach consumers in Labuhan Burung, Buer, and surrounding areas. The program confirms that MSME digitalization should begin with product readiness, concentration on one or two priority channels, and consistent content production. Further quantitative evaluation is required to measure competency improvement, sales conversion, and business sustainability.